Determinants of Foreign Exchange Reserves in Indonesia - Nelly Hutajulu (Proceedings of AICS - Social Sciences, 2017)
Foreign exchange reserves are assets of the central bank. It has saved by reserve currency like dollars, euros, yen and used for beginning international trade and finance the Indonesian economy. It saved in a Balance Payment (BOP). This study aims to determine how the influence of macroeconomic variables (inflation, exchange rate, exports, and imports) on foreign exchange reserves in Indonesia. The data used in this study during the period 2001-2015 from the Central Statistics Agency (BPS), and Bank Indonesia (BI). This research used Ordinary Least Square (OLS). Based on the analysis, the researcher found simultaneously that inflation, exchange rate, exports and imports have significant effect to the foreign exchange reserves in Indonesia. Partially inflation has no effect, exchange rate has significant effect, and export and import have significant effect to foreign exchange reserves in Indonesia.